MENINGKATKAN KEMAMPUAN ANALISIS SINTESIS SISWA MELALUI PENERAPAN PENGAJARAN LANGSUNG DENGAN METODE PROBLEM SOLVING - Haryandi, Surya; Zainuddin, Zainuddin; Suyidno, Suyidno (Universitas Lambung Mangkurat, 2013)
ABSTRACT:Â Improper learning steps resulted in low student synthesis and analytical skills in solving a physics problem or symptom. Therefore, this research is done in order to improve student synthesis and analytical skills. Specific objectives of research are: (1) achievement of lesson plans, (2) student procedural skills, (3) student learning outcomes after following learning, (4) the response of student towards learning. This type of research uses classroom action research. Data retrieval techniques through achievement test, observation, questionnaires, and documentation.Â Key word: Synthesis and analytical skills, direct instruction, problem solving, heat transfer.